Enucleation of BD-IPMN in a Transplanted Patient. A New Diagnostic/Therapeutic Approach - Del Chiaro, Marco; Rangelova, Elena; Ansorge, Christoph; Blomberg, John; Verbeke, Caroline; Segersvärd, Ralf (JOP. Journal of the Pancreas, 2012)
Context The incidence of incidentally found cystic tumors of the pancreas has increased tremendously during the last years. The diagnosis and management of these lesions remain, in many cases controversial. No data are available regarding the clinical history of these lesions in patients undergoing immunosuppressive treatment. Case report A 65-year-old woman previously liver transplanted due to familial amyloidosis. After transplantation she developed stricture of the bile duct anastomosis that was repeatedly and successful treated by endoscopy. At the pre-transplant CT-scan a suspected multifocal branch duct (BD)-IPMN of the pancreas was observed. The biggest lesion at that time was 15 mm in diameter and located in the pancreatic tail. During follow-up after transplant, a progressive increase in size of this cystic lesion was observed until the last CT in autumn 2011 when the diameter was 35 mm. No sign of degeneration (symptoms, mural nodules) were observed. Following the IAP guidelines for treatment of BD-IPMN the patient was evaluated for surgery. Due to immunosuppressive regimen, and thus related increased risk for major surgery, a surgical enucleation of the lesion for diagnostic and therapeutic purpose was done. The post-operative course was uneventful. The pathological diagnosis was BD-IPMN with low grade dysplasia. Conclusion Transplanted patients are more prone to develop complications after major surgery and at higher risk to develop cancer. Enucleation of suspected pre-malignant lesions of the pancreas may therefore be a useful approach to confirm diagnosis but also to treat this kind of lesions.